2011
DOI: 10.1093/humrep/der118
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 is involved in the remodelling of human-trophoblast-derived HTR-8/SVneo cells induced by lipopolysaccharides

Abstract: LPS may induce remodelling of the human-trophoblast-derived HTR-8/SVneo cells by increasing miR-155, acting in part through the AP-1 and NF-κB pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 40 publications
5
52
0
Order By: Relevance
“…Our previous work has demonstrated that the promoter of B-cell intergration cluster/miR-155 gene contains activator protein 1 and NF-κB binding motifs, and these 2 transcription factors contribute to LPS-induced expression of miR-155. 13 Here, we also showed that inhibitors of activator protein 1 and NF-κB significantly inhibited TNFα-induced upregulation of miR-155 in HUVECs. More importantly, we found that pretreatment of miR-155 inhibitor reversed TNFα-induced downregulation of eNOS expression, reduction of NO production in HUVECs, and impairment of Ach-induced endothelium-dependent vasorelaxation in human internal mammary arteries, suggesting that upregulation of miR-155 underlies, at least in part, the inhibitory effect of TNFα on eNOS expression.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our previous work has demonstrated that the promoter of B-cell intergration cluster/miR-155 gene contains activator protein 1 and NF-κB binding motifs, and these 2 transcription factors contribute to LPS-induced expression of miR-155. 13 Here, we also showed that inhibitors of activator protein 1 and NF-κB significantly inhibited TNFα-induced upregulation of miR-155 in HUVECs. More importantly, we found that pretreatment of miR-155 inhibitor reversed TNFα-induced downregulation of eNOS expression, reduction of NO production in HUVECs, and impairment of Ach-induced endothelium-dependent vasorelaxation in human internal mammary arteries, suggesting that upregulation of miR-155 underlies, at least in part, the inhibitory effect of TNFα on eNOS expression.…”
Section: Discussionsupporting
confidence: 57%
“…13 Here, we also found that TNFα-induced upregulation of miR-155 was partially blocked by SP600125 (a c-Jun N-terminal kinase inhibitor), pyrrolidine dithiocarbamate (a NF-κB inhibitor), or the combination of both inhibitors ( Figure 3B), indicating that activator protein 1 and NF-κB are critical for TNFα-induced miR-155 production.…”
Section: Tnfα Increased Mir-155 Expression In Huvecssupporting
confidence: 54%
“…Conversely, we and others (30,31) have repeatedly shown LPS can drive induction of the pri-155 promoter in a dose-dependent manner. Our data are additionally supported by chromatin immunoprecipitation and oligonucleotide pulldown assays displaying increased binding of Ets2 to the pri-155 promoter in the presence of LPS, Ets2…”
Section: Discussionmentioning
confidence: 60%
“…These transcription factors are implicated in trophoblast cell proliferation and differentiation, as well as pregnancy complications, such as PE [107]. Recently, an AP-1 site along with NFκB binding sites, has been identified in the miR-155 promoter [108]. Treatment of HTR8/SVneo cells with lipopolysaccharides (LPS) resulted in an increase in miR-155 levels.…”
Section: Expression Of Mirnas In Human Placentamentioning
confidence: 99%